2009
DOI: 10.1007/s11136-009-9445-7
|View full text |Cite
|
Sign up to set email alerts
|

Qualify of life and palliation predict survival in patients with chronic alveolar hypoventilation and nocturnal ventilatory support

Abstract: Seventy-three percent of patients treated for CAH with NPPV survived more than 5 years. Diagnosis and self-rated physical functioning at pre-treatment were related to survival, as were major improvements in physical functioning and global QL during NPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Of the 76 full-text articles, 38 (representing quantitative HRQOL evaluations among 28 unique cohorts of TB patients) were relevant to our review [ 1 4 , 6 , 9 , 10 , 12 21 , 26 , 29 , 31 33 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 49 , 51 – 53 , 56 , 57 , 59 , 60 ]. Studies included in the systematic review were published in English, Korean, Chinese, Spanish, and Turkish.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 76 full-text articles, 38 (representing quantitative HRQOL evaluations among 28 unique cohorts of TB patients) were relevant to our review [ 1 4 , 6 , 9 , 10 , 12 21 , 26 , 29 , 31 33 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 49 , 51 – 53 , 56 , 57 , 59 , 60 ]. Studies included in the systematic review were published in English, Korean, Chinese, Spanish, and Turkish.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven of the 28 unique cohorts reported the number of women, which corresponded to 42 % of the subjects in these studies [ 1 4 , 6 , 9 , 10 , 12 15 , 18 – 21 , 26 , 29 , 31 33 , 35 , 37 , 38 , 39 , 40 , 45 , 46 , 49 , 51 – 53 , 56 , 57 , 59 , 60 ]. Mean age (reported in 13 studies) was the most frequently reported summary measure of age [ 1 4 , 6 , 13 – 15 , 20 , 21 , 26 , 32 , 33 , 38 , 45 , 46 , 52 , 53 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…151 Patients may know little or nothing about this modality of therapy and education by referring providers and pulmonary rehabilitation personnel concerning the possible benefits of its use in hospital, at home, or in training can help avoid misunderstandings, facilitate more informed decisions, ease fears, and offer hope of palliation of symptoms to them and their families. 152,153 In patients with chronic respiratory diseases and refractory dyspnea or pain, opioid therapy may be beneficial and is recommended in the recent guideline on palliative care by the American Thoracic Society. 8 Oral, nebulized, and systemic opioids have been evaluated in controlled trials in patients with cancer and COPD.…”
Section: The Palliative Outcomes Of Pulmonary Rehabilitationmentioning
confidence: 99%
“…HRQL is known to predict mortality in cancer patients[68] and in a range of other diseases and clinical settings including HIV[9], respiratory conditions[10], cardiac surgery[11], and intensive care[12], possessing predictive power beyond that of demographic and clinical measures alone. General health and physical functioning were the most often cited domains.…”
Section: Introductionmentioning
confidence: 99%